Horizontal Force-Velocity-Power Profiling of Rugby Players: A Cross-Sectional Analysis of Competition-Level and Position-Specific Movement Demands. Issue 6 (June 2021) - Watkins, Casey M.; Storey, Adam; McGuigan, Michael R.; Downes, Paul; Gill, Nicholas D.
Abstract : Abstract: Watkins, CM, Storey, A, McGuigan, MR, Downes, P, and Gill, ND. Horizontal force-velocity-power profiling of rugby players: A cross-sectional analysis of competition-level and position-specific movement demands. J Strength Cond Res 35(6): 1576–1585, 2021—Speed and acceleration are crucial to competitive success in all levels of rugby union. However, positional demands affect an athlete's expression of force and velocity during the match. This study investigated maximal sprint performance and horizontal force-velocity (FV) profiles in 176 rugby union players participating in amateur club, professional, and international competitions. Rugby players were divided into 5 positional groups: tight-5 forwards ( n = 63), loose forwards ( n = 35), inside backs ( n = 29), midbacks ( n = 22), and outside ( n = 27) backs. Sprint performance was averaged across 2 trials of a maximal 30-m sprint, separated by a 3-minute rest. The results demonstrated differences in sprint performance and FV profile characteristics across competitions and positional groups. Specifically, both international and professional players possessed significantly faster split times and superior FV profiles than club players ( p < 0.01; effect size [ES]: 0.22–1.42). International players were significantly faster across 0–10 m than professional players ( p = 0.03; ES: 0.44–0.47), whereas professional players had faster 10–20 m times ( p = 0.03; ES: 0.37–0.41) and a more force-dominant profile ( p < 0.01; ES: 0.71–1.00). Across positions, split times decreased and maximal velocity characteristics increased in proportion with increasing positional number, with outside backs being the fastest (ES: 0.38–2.22). On the other hand, both forwards groups had more force-dominant profiles and average sprint momentum across all distances than all backs positions. Interestingly, loose forwards had a more forceful profile and slower 10-, 20-, and 30-m split times but similar maximal velocity characteristics to inside backs, highlighting unique positional demands and physical attributes. Abstract : Supplemental Digital Content is Available in the Text.